The Influence of Role Conflict, Role Ambiguity and Role Overload Against Cyberloafing Behavior - Nazarudin Nazarudin; Sulastri Sulastri (Human Resource Management Studies, 2021)
This study analyzes: (1) the effect of role conflict on cyberloafing behavior (2) the effect of role ambiguity on cyberloafing behavior (3) the effect of role overload on cyberloafing behavior (4) the effect of role conflict, role ambiguity, and role overload simultaneously on cyberloafing behavior. This study is quantitative. The population in this study is. The population in this study were employees of PT. Semen Padang in the HR and general department, the finance department, the production planning department, and the communication department, with a total of 257 people. The sampling technique was taken using proportional clustered simple random sampling where the number of samples was 156 people. Collecting data using a questionnaire with a Likert scale. The analysis technique used is through SPSS 25.0 software. The results of data processing in this study indicate that: (1) role conflict has a positive and significant effect on cyberloafing behavior among employees of PT. Semen Padang (2) role ambiguity has a positive and significant effect on cyberloafing behavior among employees of PT. Semen Padang (3) role overload has no influence and is non-significant to cyberloafing behavior in PT employees Semen Padang (4) role conflict, role ambiguity, and role overload have a positive and significant effect on cyberloafing behavior among employees of PT. Semen Padang.